The Effect of Early Mobilization on Functional Status of Stroke Patients: A Literature Review - Mustikaningrum, Retno Endarwati; Handayani, Fitria; Hastuti, Yuni Dwi; Latumanuwij, Romy; Fieten, Marloes (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2023)
Stroke impact to the altering functional status. Early mobilization is one of stroke care components that can minimize impact due to altering functional status such as weakness and paralysis in stroke patients. The review of early mobilization was proved increasing the functional status among critical illness patients. Limited review regarding the effect of early mobilization on changes in the level of functional status of stroke patients The aim the study was to determine the effect of early mobilization at the level of functional status of stroke patients. This research used the literature review with the MeSH search tool. The keywords and syntax included